Addressing Colorectal Cancer Among Alaska Native Peoples: A Community and Subject Matter Expert Symposium - Diana Redwood; Samantha McNelly; Kate Flynn; Claire Siekaniec; Charissa Habeger; Kyle Wark; Todd Takeno; Timothy Thomas (Gastro Hep Advances, 2025)
Background and Aims: Alaska Tribal health organizations are working to increase colorectal cancer (CRC) prevention and control as well as awareness of its impact among Alaska Native peoples, who have the highest rates of CRC in the world. Methods: The Alaska Native Tribal Health Consortium convened the first Alaska Native CRC Research Symposium (symposium) held June 12–13, 2023 in Anchorage, Alaska. The symposium had 3 objectives: (1) Describe the epidemiology of Alaska Native CRC, clinical practices, and risk factors; (2) Share CRC prevention research happening in Alaska; and (3) Explore future ideas to reduce Alaska Native CRC. We report on the symposium design, findings, knowledge gaps, and future directions for others seeking to combat CRC in their state or Tribal community. Results: The symposium brought together Alaska Tribal healthcare leaders, community members, clinicians, scientists, and public health professionals. A third of attendees (32%) were Alaska Native or American Indian people and/or from rural/remote Alaska (27%). The symposium consisted of 6 different scientific sessions organized around the following themes: CRC Trends in Alaska and the United States, Risk and Protective Factors, Alaska Tribal Prevention Activities, Alaska Native Research and Initiatives, Knowledge Gaps, and New Research and Other Initiatives. Conclusion: Reducing the burden of CRC among Alaska Native peoples will require persistent efforts to conduct quality research in partnership with Alaska Native communities; dedication of resources to fund research, prevention, and screening activities; and a steadfast, multisectoral commitment to addressing the persistent inequity of CRC experienced by Alaska Native peoples, families, and communities. This symposium was an important step in engaging in the collective journey to prevent CRC and promote health and wellness among Alaska Native peoples.